أليات بناء الاستراتيجيات الابتكارية في المجال الاشهاري -اقتراح نموذج مصمم لؤسسة اليد الذهبية/عنابة- - عواج, سامية; دراجي, هادية (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة إلى بناء إستراتيجية إشهارية لمطحنة –شركة- اليد الذهبية، و الخروج من خلالها بتصميم لافتة إشهارية تسمح لهذه الأخيرة بالتعريف بنفسها و عرض منتوجها و خصائصه للجمهور، و ذلك عن طريق التطرق إلى المفاهيم الأساسية التي تتعلق بمتغيرات الدراسة و إسقاطها على الميدان. و لتحقيق أهداف هذا البحث تم استخدام منهج الدراسة الميدانية الذي يسمح للباحث بدراسة طرق العمل و التفكير داخل أي تنظيم؛ بمعية المنهج الوصفي الذي يساعد في الانتقال من الميدان إلى وصف حقائق واقعية، كما تم الاعتماد على أداة الاستمارة كأداة رئيسية لتشخيص الجمهور المستهدف من هذه الدراسة -المستهلك النهائي- حيث وزعت هذه الاستمارة بطريقة عشوائية على (100 مفردة)، كما تم استخدام أداة المقابلة الشخصية كأداة مساعدة و ذلك لتسهيل عملية الحصول على المعلومات و القيام بتشخيص لوضعية الشركة. و تنقسم هذه الدراسة إلى قسمين: قسم نظري و آخر تطبيقي، حيث قامت الباحثتان بدراسة ميدانية لشركة اليد الذهبية لإنتاج الطحين – السميد - و الكائن مقرها بالمنطقة الصناعية لعلاليق البوني- ولاية عنابة- و توصلتا من خلال هذه الدراسة الميدانية إلى أن الشركة تعاني من مشكل إتصالي خاصة مع الجمهور الخارجي لها (المستهلك). ولهذا تم اقتراح فكرة بناء إستراتيجية إشهارية لهذه الشركة حيث تعتمد هذه الأخيرة على اللافتة الإشهارية كقناة لنقل رسالتها، هذه الأخيرة التي قد تساعد الشركة على تحسين وضعتها في السوق كما توفر فرص أرقى و أكثر لتشجيع الإبداع المستمر على المدى الطويل للطلبة في مجال الإشهار و العلاقات العامة. Abstract : This study aims to set up an advertising strategy for the company "THE GOLDEN HAND" in order to clear the design of an advertising poster allowing the latter to identify itself, and to leave the anonymity of exposing its products and characteristics to the general public, and this by evoking the main concepts related to the variables of the study and have them projected on the ground. In order to achieve the objectives of this study, we used the practical study method which allows the researcher to study the modes of work and reflection within any organization with the use of the descriptive method which promotes the transition from the field to the description of real facts. Similarly, we adopted the questionnaire as the main tool to diagnose the target audience of this study (the final consumer), the latter was distributed randomly to (100 targeted individuals), as well as the personal interview tool. was used as a back-up tool, to facilitate the operation of the acquisition of information and to diagnose the situation of the company. This study is divided into two parts: a theoretical part, and another practice, because the researchers have carried out a practical study of the company "LA MAIN D'OR" for the production of flour and semolina, and whose headquarters is located industrial area LALALIG -EL BOUNI- ANNABA. Through this practical study, we have achieved the following result: this company suffers from the problem of lack of communication with its external public (the consumer). For this reason, the idea of setting up an advertising strategy for this company has been proposed so that it adopts the advertising poster as a medium to transmit its message, which enables it to improve its situation. In the marketplace, likewise, this allows for better opportunities to encourage long-term sustainable innovation among students in the field of advertising and public relations.
Mechanisms for building innovative strategies in the field of advertising -Proposed model designed for the Golden Hand Foundation / Annaba
مقال
Keywords: المؤسسة الإستراتيجية، الإشهار، الإستراتيجية الإشهارية، اللاّفتة الإشهارية.; Organization Strategy , Advertising , Advertising strategy, Advertising banner